Approaches of Data Warehousing and Their Applications: A Review (International Journal of Innovative Research in Computer Science & Technology, 2022)
A data warehouse, DW in short is a huge  repository of corporate data that is employed to aid an  organization's decision-making. The data warehouse idea  has been around throughout eighties, while it was created to  assist in the transformation of data from just enabling  activities to fueling judgment assistance capabilities that  disclose business insight. The huge volume of data in data  stores originates from a variety of sources, including  interior services like branding, selling, and treasury,  customer-facing services, and outsourced systems, besides  several. On a scientific basis, a DW gathers data from  various apps and platforms on a regular basis; the data is  then formatted and imported to match the data currently in  the storehouse. This generated content is stored in the  DW so that decision makers may access it. The frequency  with which data pulls happen, how data is organized, and so  on will vary relying on the needs of the company. The  procedure of mining data from a basic system or excavating information from a huge quantity of data is known as data  warehousing. It is generally known as ETL, which stands  for extract, transform, and load. This paper discusses the  following topics: an overview of Datawarehouses, different  Datawarehouse design approaches and their benefits and  drawbacks, different sorts of pulling out techniques in  Datawarehouses, characteristics of Datawarehouses,  dissimilar doles of data warehousing, unalike components  used in DW, and data warehousing usages.
Keywords: Datawarehouse Applications; Datawarehouse Characteristics; Datawarehouse Components; Datawarehouse Design; Datawarehouse; Extraction MethodS